2020
DOI: 10.1080/15384101.2020.1717043
|View full text |Cite|
|
Sign up to set email alerts
|

The protective effects of microRNA-26a in steroid-induced osteonecrosis of the femoral head by repressing EZH2

Abstract: Recently, the role of microRNAs (miRs) in human diseases has been verified. This study was determined to explore the protective effects of microRNA-26a (miR-26a) in steroid-induced osteonecrosis of the femoral head (SONFH) with the involvement of enhancer of zeste homologue 2 (EZH2).Femoral head (FH) samples from SONFH patients and patients with femoral neck fracture were collected, and rat SONFH models were established by Escherichia coli endotoxin combining with large dose steroid pulse assay. The hemorheolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“… Breast cancer [ 145 ] Head and neck cancer [ 100 ] Oral cancer [ 142 ] Prostate cancer [ 143 ] Pancreatic cancer [ 144 ] Down-regulation Regulation of PTEN, CSC marker Lin28b, suppression of EMT and CSC phenotype [ 142 – 144 ] Blockage of Wnt signaling and suppressing self-renewal and stemness of CSCs [ 145 ] Inhibition of EZH2, and suppression of CSC characteristics [ 146 ] miR-26a Tumor suppressive Anti-invasive, stemness inhibitory [ 147 – 149 ] Gastric cancer [ 150 ] Hepatocellular carcinoma [ 149 ] Breast cancer, prostate cancer, pancreatic cancer, nasopharyngeal carcinoma [ 118 ] ? Suppression of HOXC9 and inhibits its metastatic and stemness features of self-renewal [ 150 ] Inhibition of EZH2, and suppression of CSC characteristics [ 147 , 148 ] and EMT [ 149 ] …”
Section: The Effect Of Hypoxia On Cancer Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“… Breast cancer [ 145 ] Head and neck cancer [ 100 ] Oral cancer [ 142 ] Prostate cancer [ 143 ] Pancreatic cancer [ 144 ] Down-regulation Regulation of PTEN, CSC marker Lin28b, suppression of EMT and CSC phenotype [ 142 – 144 ] Blockage of Wnt signaling and suppressing self-renewal and stemness of CSCs [ 145 ] Inhibition of EZH2, and suppression of CSC characteristics [ 146 ] miR-26a Tumor suppressive Anti-invasive, stemness inhibitory [ 147 – 149 ] Gastric cancer [ 150 ] Hepatocellular carcinoma [ 149 ] Breast cancer, prostate cancer, pancreatic cancer, nasopharyngeal carcinoma [ 118 ] ? Suppression of HOXC9 and inhibits its metastatic and stemness features of self-renewal [ 150 ] Inhibition of EZH2, and suppression of CSC characteristics [ 147 , 148 ] and EMT [ 149 ] …”
Section: The Effect Of Hypoxia On Cancer Stem Cellsmentioning
confidence: 99%
“…Tumor suppressive Anti-invasive, stemness inhibitory [147][148][149] Gastric cancer [150] Hepatocellular carcinoma [149] Breast cancer, prostate cancer, pancreatic cancer, nasopharyngeal carcinoma [118] ? Suppression of HOXC9 and inhibits its metastatic and stemness features of self-renewal [150] Inhibition of EZH2, and suppression of CSC characteristics [147,148] and EMT [149] some evidence from its role in cancer growth. However, HIF-1α may temporally maintain cancer cells in a quiescent state and conserve their survival as long as oxygen supply is available, where they become more invasive.…”
Section: Pro-oncogenicmentioning
confidence: 99%
“…For example, miR-155-5p was found to be significantly downregulated in ONFH samples [ 16 ]. miR-148a-3p [ 17 ], miR-23b-3p [ 18 ], and miR-26a [ 19 ] were all reported to play a protective role against ONFH. Recent advancement of genome-wide profiling approaches, such as gene microarray and RNA-sequencing technology, enhances the understanding of miRNA and gene expression profiles in the context of ONFH, providing opportunity to identify novel biomarkers and therapeutic targets for ONFH [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…SOX5 has been reported to increase the expression of EZH2 at the mRNA and protein levels, while the knock-down of SOX5 reduces the expression of EZH2 [ 15 ]. The downregulated expression of EZH2 induces angiogenesis and osteogenesis [ 17 , 20 ]. To further explore the relationship between SOX5 and EZH2 in ONFH, we initially analyzed the GSE74089 dataset and found that EZH2 was notably upregulated in the ONFH samples (Fig.…”
Section: Resultsmentioning
confidence: 99%